Transformasi Personal Branding Islami dalam Menghadapi Tantangan Era Digital - Annisya Nur Fitrianty; Tyrra Aleyda Maulani; Raden Muhammad Hilmi Maulana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of digital technology has significantly transformed the way individuals build their identities and communicate in the public sphere. In this context, personal branding has become an important aspect for young people to develop a positive self-image while utilizing social media wisely and productively. This study aims to analyze the transformation of Islamic personal branding as a strategy for building a digital identity based on Islamic values. The research employed a descriptive qualitative approach through a literature review by examining various scientific journals, books, and academic sources related to Islamic personal branding, digital communication, and social media ethics. The findings reveal that Islamic personal branding is not merely focused on popularity and self-promotion but also emphasizes moral values such as honesty, responsibility, integrity, politeness, and Islamic identity in digital interactions. The transformation of Islamic personal branding can be implemented through the creation of positive and educational content, enhancement of digital literacy, respectful communication, and the avoidance of excessive flexing behavior on social media. The study implies that Islamic values can serve as a strong foundation for developing a professional, ethical, authentic, and socially beneficial digital identity in the era of digital transformation.